Professional Learning Through Transitions and Transformations Teacher Educators' Journeys of Becoming - Williams, Judy; Hayler, Mike (Self-Study of Teaching and Teacher Education Practices, 2016)
Through a narrative inquiry approach, this book examines the personal professional journeys of teacher educators who have undertaken self studies, and/or researched the professional development of teacher educators. The theme of the book is how change, through professional transitions and transformations and notably, through self study research, has shaped the professional identities and practices of these teacher educators. Each chapter is an exploration of how the author/s 'became' teacher educators in relation to personal and/or professional transitions, such as transitioning from teacher to teacher educator; moving between different institutional and geographic contexts; or from changes in philosophical, policy and/or pedagogical understandings over time. Each narrative draws on the author's self study experience, and develops their knowledge further by presenting the wisdom they have gained over their career as teacher educators. The book concludes with a discussion of the connections between the diverse experiences of the authors, and what can be learned from their accumulated wisdom about what is means to become a teacher educator in a dynamic and ever-changing educational landscape.  .